Are the conserved sequences in segment 1 of gelsolin important for binding actin? (The Rockefeller University Press, 1992)
The minimal region required for actin binding in the smallest of the three domains of gelsolin (termed Segment 1 or S1) was previously defined by deletion mutagenesis as residues 37-126. Further analysis of NH2-terminal deletions here redefines the minimal functional core as residues 41-126. Amino acid substitutions within this core further elucidate the nature of the interaction of segment 1 with actin. Of 26 point mutants analyzed, 14 reduced the affinity for actin. The charged residues His 119, Arg 120, Glu 121, and Gln 123 appear to be involved in direct interaction with actin. Substitutions of Leu 108, Leu 112, and Val 117 by polar groups all affect the structural stability of segment 1 and thereby reduce binding affinity. In addition replacement of Glu 126 by aspartic acid modifies the physical properties of segment 1 and weakens binding. We have further shown that changing charged residues within the highly conserved pentapeptide sequence LDDYL (residues 108-112) has no effect on actin binding. This sequence, found in a number of different actin binding proteins, does not therefore constitute part of the interaction site. Similarly, substitution of the two acidic residues by basic ones within the DESG motif of segment 1 (residues 96-99, but also found near the COOH terminus of actin) does not impair binding. These results show the dangers of predicting functional sites on the basis of conserved sequences.